Bacterial and abiogenic carbonates formed in caves–no vital effect on clumped isotope compositions - Demény, Attila (PLoS One, 2021)
Speleothems (dominated by cave-hosted carbonate deposits) are valuable archives of paleoclimate conditions. As such, they are potential targets of clumped isotope analyses that may yield quantified data about past temperature variations. Clumped isotope analyses of stalagmites, however, seldom provide useful temperature values due to various isotope fractionation processes. This study focuses on the determination of the microbially induced vital effect, i.e., the isotope fractionation processes related to bacterial carbonate production. A cave site with biologically mediated amorphous calcium carbonate precitation was selected as a natural laboratory. Calcite deposits were farmed under a UV lamp to prevent bacterial activity, as well as under control conditions. Microbiological analyses and morphological investigations using scanning electron microscopy showed that the UV lamp treatment effectively reduced the number of bacterial cells, and that bacterial carbonate production strongly influenced the carbonate’s morphology. Stable oxygen isotope analyses of calcite and drip waters, as well as clumped isotope measurements revealed that, although most of the studied carbonates formed close to oxygen isotope equilibrium, clumped isotope Δ(47) values varied widely from equilibrium to strongly fractionated data. Site-specific kinetic fractionations played a dominant role in the distribution of Δ(47) values, whereas bacterial carbonate production did not result in a detectable clumped isotope effect.